Biomass Partitioning of Cassava (Manihot esculenta Crantz) at Various Doses of Nitrogen Fertilization - Gili, Oktaviana Rosario Sere; Suwarto; Hartono, Arief; Herdiyeni, Yeni (Department of Agronomy and Horticulture, IPB University, 2025)
The distribution of carbohydrates across different plant organs, or carbohydrate partitioning, is a vital indicator of nitrogen use efficiency and resource allocation in plants. This study aimed to evaluate the impact of varying nitrogen fertilization rates on carbohydrate partitioning in cassava (Manihot esculenta Crantz). A randomized block design was used with six nitrogen dose treatments (0, 45, 90, 135, 180, 225 kg.ha-1) and four replications. Parameters observed included dry weight and carbohydrate distribution in roots, stems, leaves, root tubers, and petioles over eight months after planting (MAP). Results indicated that nitrogen fertilization significantly influenced cassava plants’ dry weight and carbohydrate partitioning, with optimal nitrogen doses varying by plant organ and growth stage. Nitrogen application enhanced carbohydrate allocation to root tubers, particularly from 3 to 8 MAP.